2020
DOI: 10.2139/ssrn.3628004
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of Phase Transformations in Additive Manufacturing of Alloy 718

Abstract: This paper presents a discussion on the phase-transformation aspects of additively manufactured Alloy 718 during the additive manufacturing (AM) process and subsequent commonly used post-heat treatments. To this end, fundamental theoretical principles, thermodynamic and kinetics modeling, and existing literature data are employed. Two different AM processes, namely, laser-directed energy deposition and electron-beam powder-bed fusion are considered. The general aspects of phase formation during solidification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(86 reference statements)
1
6
0
Order By: Relevance
“…The high hardness and significant precipitation of c 00 phase as shown in Fig. 10 achieved through ST with FC reveals interesting prospects in tailoring cooling rate after ST as an alternative to carrying out a separate subsequent aging treatment as also recently reported by Kumara et al [40]. For instance, in oil-field applications, Special Metals Corp. has suggested a maximum hardness of Alloy 718 to be 40 HRC (382 kgf/mm 2 [58]) [59] which is significantly below the peak hardness of the material (* 500 kgf/mm 2 ) [18].…”
Section: Potential To Design Shorter Tailored Posttreatment For Ebm Asupporting
confidence: 59%
See 2 more Smart Citations
“…The high hardness and significant precipitation of c 00 phase as shown in Fig. 10 achieved through ST with FC reveals interesting prospects in tailoring cooling rate after ST as an alternative to carrying out a separate subsequent aging treatment as also recently reported by Kumara et al [40]. For instance, in oil-field applications, Special Metals Corp. has suggested a maximum hardness of Alloy 718 to be 40 HRC (382 kgf/mm 2 [58]) [59] which is significantly below the peak hardness of the material (* 500 kgf/mm 2 ) [18].…”
Section: Potential To Design Shorter Tailored Posttreatment For Ebm Asupporting
confidence: 59%
“…An earlier study on wrought Alloy 718 quantified d phase and showed higher amount of d phase formation after ST at 950°C compared to 975°C; both treatments performed for a constant duration of 2 h [39]. Simulation results have also shown higher equilibrium volume fraction of d phase at 954°C than at 980°C [40]. Therefore, depending on the required microstructural properties appropriate ST conditions should be employed, as increase in d phase content has been reportedly associated with reduced amount of strengthening phase c 00 [49], because precipitation of both d and c 00 phases compete for available Nb in the material [50].…”
Section: Solution Treatmentmentioning
confidence: 88%
See 1 more Smart Citation
“…In non-equilibrium solidification, the γ matrix begins to solidify when the temperature is below the liquidus temperature during the first several thermal cycles. The segregation of Inconel 718 component elements changes the driving force of phase formation, which leads to the formation of Laves phases in the interdendritic region [60]. It has been reported that Laves formation is related to slow solidification at a low cooling rate [61].…”
Section: Discussionmentioning
confidence: 99%
“…The austenite phase is strengthened by precipitating γ' (Ni (Al, Ti)) and γ'' (Ni 3 Nb) phases. However, it also forms some harmful intermetallic phases at the time of processing such as δ (Ni 3 Nb) with orthorhombic DO a structure and laves (Ni, Fe, Cr) 2 (Nb, Mo, Ti) phases with a hexagonal crystal structure due to more segregation of Nb and Mo elements [4][5][6][7]. The desired properties of the alloy can be restored by eliminating the intermetallic phases and increasing the presence of strengthening phases [8].…”
Section: Introductionmentioning
confidence: 99%